PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI, DAN PERSEPSI KEAMANAN TERHADAP KEPUASAN PENGGUNA APLIKASI E-COMMERCE - Tanaya, Alicia; Setiawan, Amelia; Wirawan, Samuel; Djajadikerta, Hamfri (Jurnal Riset Akuntansi, 2023)
The presence of the COVID-19 pandemic has resulted in changes of people's shopping activities habits. It is reflected in the increment in the number of visits to e-commerce applications. However, the loyalty level of e-commerce users tends to be low. Therefore, user satisfaction is very important to increase their loyalty to the application. This study aims to determine the effect of system quality, information quality, and perceived security on e-commerce application user satisfaction. This research was conducted by collecting 130 respondents' data through Google Form. Data processing and analysis techniques were carried out using hypothesis testing and multiple regression analysis. The results of this study indicate that system quality and perceived security partially affect the satisfaction of e-commerce application users, while the effect of information quality has no statistical effect on e-commerce application user satisfaction. Simultaneously, system quality, information quality, and perceived security affect the satisfaction of e-commerce application users.